Molecular insight into thymoquinone mechanism of action against Mycobacterium tuberculosis - Jankowski, Grzegorz; Sawicki, Rafał; Truszkiewicz, Wiesław; Wolan, Natalia; Ziomek, Marcin; Hryć, Benita; Sieniawska, Elwira (Frontiers in Microbiology, 2024)
Natural products are promising antimicrobials, usually having multiple and different cellular targets than synthetic antibiotics. Their influence on bacteria at various metabolic and functional levels contributes to higher efficacy even against drug-resistant strains. One such compound is a naturally occurring p-benzoquinone – thymoquinone. It is effective against different bacteria, including multidrug-resistant and extremely drug-resistant Mycobacterium tuberculosis. Its antibacterial mechanism of action was studied in several bacterial species except mycobacteria. To get an insight into the antimycobacterial activity of thymoquinone at the molecular level, we performed metabolomic and transcriptomic analyzes of bacteria exposed to this compound. The expression of genes coding stress-responsive sigma factors revealed that thymoquinone rapidly induces the production of sigE transcripts. At the same time, prolonged influence results in the overexpression of all sigma factor genes and significantly upregulates sigF. The metabolomic analysis confirmed that the antimycobacterial activity of thymoquinone was related to the depletion of NAD and ATP pools and the downregulation of plasma membrane lipids. This state was observed after 24 h and was persistent the next day, suggesting that bacteria could not activate catabolic mechanisms and produce energy. Additionally, the presence of a thymoquinone nitrogen derivative in the bacterial broth and the culture was reported.